Numerical analysis of axisymmetric and planar sudden expansion flows for laminar regime - Dagtekin, Ihsan; Unsal, Mazhar (Wiley-Blackwell, 2011)
In this study, the Navier-Stokes equations are solved numerically for axisymmetric and planar sudden expansion flows. The flow is considered laminar and steady state, and the fluid is incompressible. Finite difference equations are obtained using a control volume method in a non-staggered grid arrangement, and solved by line-by-line TDMA technique using the SIMPLEM (SIMPLEM-Modified) algorithm. Calculations are performed for higher expansion ratios, beta, ranging from 1.5 to 10 and Reynolds numbers from 0.1 to 500. Results are presented in terms of streamlines, relative eddy intensity, location of the eddy center, and the eddy reattachment length depending on Re number and beta values for both axisymmetric and planar sudden expansions. It is aimed to provide a picture of the effects of high values of expansion ratio and Reynolds number on the sudden expansion flow. As a result, it is found that the flow characteristics keep their structure for both higher expansion ratios and higher Reynolds numbers. Further, correlations were developed for the nondimensional eddy reattachment length, location of the eddy center and the relative eddy intensity, which have agreeable results to the computed results available from the literature. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: sudden expansion; laminar flow; non-staggered grid; axisymmetric flow; planar flow